Peripheral KV7 channels regulate visceral sensory function in mouse and human colon. Issue 1 (May 2017) - Peiris, Madusha; Hockley, James RF; Reed, David E; Smith, Ewan St. John; Bulmer, David C; Blackshaw, L Ashley
Background: Chronic visceral pain is a defining symptom of many gastrointestinal disorders. The KV 7 family (KV 7.1–KV 7.5) of voltage-gated potassium channels mediates the M current that regulates excitability in peripheral sensory nociceptors and central pain pathways. Here, we use a combination of immunohistochemistry, gut-nerve electrophysiological recordings in both mouse and human tissues, and single-cell qualitative real-time polymerase chain reaction of gut-projecting sensory neurons, to investigate the contribution of peripheral KV 7 channels to visceral nociception. Results: Immunohistochemical staining of mouse colon revealed labelling of KV 7 subtypes (KV 7.3 and KV 7.5) with CGRP around intrinsic enteric neurons of the myenteric plexuses and within extrinsic sensory fibres along mesenteric blood vessels. Treatment with the KV 7 opener retigabine almost completely abolished visceral afferent firing evoked by the algogen bradykinin, in agreement with significant co-expression of mRNA transcripts by single-cell qualitative real-time polymerase chain reaction for KCNQ subtypes and the B2 bradykinin receptor in retrogradely labelled extrinsic sensory neurons from the colon. Retigabine also attenuated responses to mechanical stimulation of the bowel following noxious distension (0–80 mmHg) in a concentration-dependent manner, whereas the KV 7 blocker XE991 potentiated such responses. In human bowel tissues, KV 7.3 and KV 7.5 were expressed in neuronal varicosities co-labelled with synaptophysin and CGRP, and retigabine inhibited bradykinin-induced afferent activation in afferent recordings from human colon. Conclusions: We show that KV 7 channels contribute to the sensitivity of visceral sensory neurons to noxious chemical and mechanical stimuli in both mouse and human gut tissues. As such, peripherally restricted KV 7 openers may represent a viable therapeutic modality for the treatment of gastrointestinal pathologies.